Persistent cough after pulmonary resection: Minor issue, major hurdle - Xuefeng Sun; Zihua Lan; Qiuling Shi; Hansheng Wu; Guojie Lu; Yuan Qiu; Yong Tang; Guibin Qiao (Heliyon, 2024)
Background: Persistent cough is one of the most common complications following pulmonary resection, that impairs patients’ quality of life and prolongs recovery time. However, a comprehensive review of persistent cough after pulmonary resection (CAP) has not been performed. Methods: A literature search of PubMed/MEDLINE, Web of Science, and Embase database was conducted for persistent-CAP up to June 2023. Subsequent qualitative systematic review focused on definition, risk factors, prevention, and treatment of persistent-CAP. Results: Persistent-CAP stands as a prevalent postoperative complication subsequent to pulmonary resection procedures. with an incidence of 24.4–55.0 %. Although persistent-CAP has a minor impact on survival, this condition is of critical importance because it presents a major hurdle in recovery after surgery. In this review, we proposed a systemic definition for persistent-CAP based on available evidence and our own data. Several assessment tools used to assess severity of persistent-CAP are also introduced. Risk factors associated with persistent-CAP are explored, including surgical approaches, resection extent, surgical site, lymph node dissection, postoperative gastroesophageal acid reflux, tracheal intubation anesthesia, preoperative comorbidity, and sex among others. Surgical and anesthesia preventions targeting risk factors to prevent persistent-CAP are elaborated. A number of studies have shown that a multidisciplinary approach can effectively relieve persistent-CAP. Conclusions: Although the mechanisms underlying persistent-CAP are still unclear, existing studies demonstrated that persistent-CAP is related to surgical and anesthesia factors. Therefore, in the future, prevention and treatment should be developed based on risk factors to overcome the hurdle of persistent-CAP.